2014
DOI: 10.4236/jmp.2014.57062
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure Analysis of the Configuration System of V II. Part II: Odd-Parity Levels

Abstract: The 3d 3 4p, 3d 3 5p and 3d 2 4s4p odd configurations of the V II spectrum have been reanalysed and three 3d 2 4s4p triplets are assigned higher energies than previously proposed. We have determined the fine structure parameters, the largest and next largest eigenvector percentages of levels, their calculated Landé gJ-factors and predicted positions for missing experimental levels up to 100,000 cm −1 for the 3d 2 4s4p configuration. Furthermore for the first time a hyperfine structure (HFS) parametric treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…means that ab initio lifetime values may help out directly, without introducing weighting factor, in the absence of experimental data. We note that in Table 3 we replaced the level 3d 3 (a 4 F) 4p z 3 D 1 with 3d 3 (a 4 F) 4p z 5 F 1 as corrected in [6].…”
Section: II Lifetime Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…means that ab initio lifetime values may help out directly, without introducing weighting factor, in the absence of experimental data. We note that in Table 3 we replaced the level 3d 3 (a 4 F) 4p z 3 D 1 with 3d 3 (a 4 F) 4p z 5 F 1 as corrected in [6].…”
Section: II Lifetime Considerationsmentioning
confidence: 99%
“…Furthermore the 3d 3 4p, 3d 3 5p and 3d 2 4s4p odd configurations for the same ion spectrum have been reanalysed and for the first time an hfs parametric treatment, involving levels of these 3 configurations, has been carried out. The main oneelectron hfs values, for both parities, are gathered and shown in Table 1; one can find the other mono-electronic parameters in [5,6]. To extract magnetic dipole A-values from experimental hfs splitting the electric quadrupole hfs B factors preferably were fixed deliberately to zero in [1,2], because the electric quadrupole moment of 51 V is very small: À 0.05b.…”
Section: II Hyperfine Structure Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore the accuracy of the amplitude of the energy level eigenvector is known to have particularly a strong influence on the determination of the effective mono-electronic hyperfine structure parameters deduced from magnetic dipole A and electric quadrupole B constants, experimentally obtained. For these reasons we propose to extend previous fs studies, using a method successfully tested for atoms: Si I [31], Hf I [32], Zr I [33], and ions: Nb II [34] Ta II [35], V II [36]. This method should find particular application for systems composed of many Rydberg configurations mutually interacting.…”
Section: Fine Structure Considerations For Odd-parity Levelsmentioning
confidence: 99%
“…The last but not the least work was done by Hassini et al [8] who reported 138 levels derived from 617 spectral lines in the range 2536 to 24 786 cm −1 . The method applied here for fine and hyperfine structure studies was successfully used previously as regards neutral and singly ionized atoms: Zr I, Hf I, Nb II, Ta II, V II, Ti II [34][35][36]44,45], gathering the set of their studied configurations in model space when it was possible. In the fs calculations we took into account the basis setup consisted of the 7 interacting configurations: 5s 2 5p 2 6s, The spin-orbit integrals ξ nd and ξ 5p effect the interactions with distant configurations.…”
Section: Fine Structure Considerations For Even-parity Levelsmentioning
confidence: 99%